2000
DOI: 10.1006/rtph.2000.1378
|View full text |Cite
|
Sign up to set email alerts
|

Hazard Identification and Dose Response of Ingested Nickel-Soluble Salts

Abstract: People can ingest soluble nickel compounds as a normal constituent of food or as a contaminant in drinking water. This paper presents an assessment of the noncancer and cancer human health risks from ingestion of soluble nickel compounds. A reference dose (RfD) of 8 x 10(-3) mg Ni/kg/day in addition to the amount in food was calculated, based on albuminuria in female rats exposed to nickel sulfate in drinking water for 6 months (A. Vyskocil et al., 1994, Hum. Exp. Toxicol. 13, 689-693). This RfD is comparable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 36 publications
0
12
0
3
Order By: Relevance
“…These lines of evidence clearly indicate that insoluble nickel compounds are potent carcinogens, while soluble nickel compounds are less potent. Accordingly, the insoluble nickel compounds are classified as a human carcinogen, while soluble nickel compounds are considered as “not classifiable as a human carcinogen” (ACGIH, 1998) or “the carcinogenicity of soluble nickel compounds cannot be determined” (Haber et al, 2000a,b).…”
mentioning
confidence: 99%
“…These lines of evidence clearly indicate that insoluble nickel compounds are potent carcinogens, while soluble nickel compounds are less potent. Accordingly, the insoluble nickel compounds are classified as a human carcinogen, while soluble nickel compounds are considered as “not classifiable as a human carcinogen” (ACGIH, 1998) or “the carcinogenicity of soluble nickel compounds cannot be determined” (Haber et al, 2000a,b).…”
mentioning
confidence: 99%
“…Similar contrasting assessments were made the following year. In 1999, Beraterkreis Toxikologie in Germany recommended a category C1 classification (substances known to be carcinogenic to man) for water-soluble nickel compounds (6), whereas the Toxicological Excellence in Risk Assessment group conducting a risk assessment for Health Canada, U.S. Environmental Protection Agency, and the Metal Finishers Association of Southern California concluded that the "carcinogenicity of soluble nickel compounds cannot be determined" (7,8).…”
mentioning
confidence: 99%
“…Diese Referenzdosis basiert auf Toxizitätsstudien bei Ratten, denen Ni in hohen Dosen (80 mg Ni 2+ /kg KG/Tag bzw. 7,6 mg Ni 2+ /kg KG/Tag) im Trinkwasser über einen Zeitraum von 2 Jahren oder 6 Monaten verabreicht wurde und als Nebenwirkung eine Gewichtsabnahme [30] bzw. eine verminderte glomeruläre Funktion mit Albuminurie [93] auftraten.…”
Section: Zusammenfassende Betrachtungunclassified
“…Das Schwermetall Ni sollte jedoch nicht nur mit der Auslösung einer Allergie assoziiert werden: Außer über die Haut besteht ein täglicher Ni-Kontakt durch Aufnahme von Ni über die Luft, Nahrung und das Trinkwasser, wobei die tägliche Ni-Zufuhr durchschnittlich 70 µg mit der Nahrung und 2 µg mit dem Trinkwasser beträgt [30]. Eine erhöhte orale Ni-Exposition, z.…”
unclassified